Diversity and Inclusion: Are We Nearly There Yet? - Eikhof, Doris Ruth (Taylor & Francis, 2023)
This book provides the first compact knowledge base on diversity & inclusion (D&I) targets in the UK screen industries. Drawing on new, in-depth industry research and progressive theoretical voices, the book will help readers understand what D&I targets are and what they could be in the future.